Prevalence, Molecular detection and Therapeutic efficacy against Aspergillosis in Indigenous chickens in Bangladesh - Mst Aireen Akter; Md Shajedur Rahman; Nazmi Ara Rumi; Md Masuk Rahman Kingshuk; Hemayet Hossain; Md Nurnoby Islam (Veterinary Integrative Sciences)
In Bangladesh, a significant challenge of raising traditional chicken breeds during the early stages of chicks is brooder pneumonia, a fungal disease primarily caused by Aspergillus spp. The prevalence, risk factors, and appropriate therapeutic measures for indigenous chicken have not been thoroughly explored, and this study was aimed to investigate these in native chicken. A cross-sectional study was conducted in the Joypurhat district of Bangladesh from November 2022 to October 2023, involving a sample size of 394 birds. The primary focus was post-mortem analysis, with suspected samples cultured on Sabouraud dextrose agar (SDA) medium, followed by PCR assay. The prevalence of Aspergillosis was found to be 12.18% (n = 48/394), with rates of 11.24% (n = 10/89) for Naked Neck and 12.46% (n = 38/305) for Native breeds. The higher prevalence among chicks aged 0–15 days (18.96%) was found. Aspergillus fumigatus was identified as the most prevalent fungal species. Multivariate logistic regression analysis identified three significant risk factors: age (0–15 days, OR = 5.38), season (winter, OR = 3.55), and litter condition (Moist, OR = 14.88). In the experimental infection groups, Group B treated with Itraconazole showed a significantly lower overall recovery time and mortality percentage (P<0.05). The therapeutic measures indicated that Itraconazole, in combination with Toxin Binder (Two-Plus Vet), NSAID drug (Paracetamol), and litter disinfectant (Blue Vitriol), was the most effective against Aspergillosis in native chickens. The findings of this study hold promise for the development of native chicken breeds, offering insights that can be applied to achieve sustainable poultry production in Bangladesh.